IMPROVING THE DESIGN OF HOPPER WAGONS FOR TRANSPORTING GRAIN (Transport systems and technologies, 2018)
An important focus of implementation requirements for rolling stock is forming a new generation of truck fleet based models domestically produced cars that have the current level of technical – economic and operational performance. Most suited for transporting grain, is hopper wagons. It is therefore necessary to reduce the number hopper wagons with expired service life and creating promising models hopper wagons of new generation. Research design features hopper wagons carried out by examining the design documentation for grain wagons from different manufacturers, as well as the materials of scientific publications with data on developers obtained in the theoretical and experimental research results. As the body of the car is a complex statically undeterminedsystem to provide intensive work of bearing elements respectively receive the minimum design metal traditional methods of designing difficult. The focus of development is given to further improving the design of car-hopper by DIC, which can provide performance requirements for modern innovative rolling stock.
Keywords: design, hopper wagons, grain haulage, innovation.